PENGARUH MATA KULIAH AQIDAH AKHLAK TERHADAP NILAI BUDAYA ISLAMI MAHASISWA DI UNIVERSITAS MUHAMMADIYAH SUKABUMI - Ika Sofia Rizqiani; Fenty Sukmawaty (AL-ULUM : Jurnal Ilmu Sosial dan Humaniora, 2023)
Moral education in an era full of technological sophistication is needed so that life is not arbitrary. If the morals of youth, especially ummi students, do not have good morals, it is difficult for lecturers to create the next generation of Islamic culture. Religion and culture influence each other. Religion affects cultures, groups, communities, and ethnic groups. Culture tends to change which has implications for the authenticity of religion. The methodology of this research uses the distribution of questionnaires and filling out questionnaires aimed at students who have followed the Aqidah Morals course using a quantitative approach. The method used is descriptive associative method. This research uses descriptive because it is described based on the results of facts in the field. There are three variables, namely Y Islamic culture, XI course values, and X2 understanding. The Regression Model/Equation Y -2.404 + 1.005x₁ + 0964x₂ Y Culture X₁ Value X₂ Understanding With the regression model above, it is known if the value and understanding are constant (zero ) then the Islamic culture of students at UMMI will have a negative value, so that it can be concluded "Students' values and understanding of Aqidah Akhlak courses play an important role in building Islamic culture of students at UMMI." become a person's culture and habits. So that the culture of having good morals becomes a good culture, both for individuals as servants of God, or as social beings. Research can be a tip to build and create students to become students who have Islamic culture and have good morals.